Abstinence related training needs for youth in the context of HIV/AIDS in Newcastle Uniting Presbyterian Church - Mpofu, Buhle (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.